Antúnez, S., Carmo, LI. M. del, Imbernou, F., Parcerisa, A., Zabala, A. (1991). Del proyecto educativo a la programación de aula. - Sanahuja Costafreda, Nuria (Revista Complutense de Educación, 1992)
Sin resumen